Climate-Related and Environmental Risks for the Banking Sector in Latin America and the Caribbean : A Preliminary Assessment - Calice, Pietro (World Bank, Washington, DC, 2021)
There is increasing recognition that climate-related and environmental risks are a source of financial risks. Using publicly available data, this paper attempts a preliminary estimation of the physical and transition risks for the banking sector in a sample of economies in Latin America and the Caribbean. The results show that exposure to floods, compounded by high loan concentration in and around countries’ capital cities, represents the most important source of credit risk for the banking sector. After large-scale natural disasters, banks’ nonperforming loans increase by up to 1.4 percentage points in affected provinces. The results also show that banks in the region are exposed to transition risks, especially in Argentina, Bolivia, Paraguay, and Uruguay, due to their high lending to the agriculture sector, which is the largest emitter of greenhouse gases in the countries. Firms operating in transition-sensitive sectors already present signs of financial stress, especially those in the fossil fuel and agriculture sectors. Overall, the results demonstrate the importance for financial authorities in the region to advance in the integration of climate-related and environmental risks in their work.